2024
DOI: 10.35848/1347-4065/ad2302
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution dynamics of poly(4-hydroxystyrene-co-methacrylic acid) in tetraalkylammonium hydroxide aqueous solutions

Yutaro Iwashige,
Kyoko Watanabe,
Yuko Tsutsui Ito
et al.

Abstract: The resist materials and their lithography processes are essential for achieving further miniaturization in the semiconductor microfabrication. In the sub-20 nm half-pitch region, the development process becomes particularly important due to the occurrence of stochastic defects (pinching and bridging). However, the details of dissolution dynamics are still unclear. In this study, we investigated the dissolution dynamics of poly(4-hydroxystyrene-co-methacrylic acid) (PHSMA) films in tetraalkylammonium hydroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This shoulder is considered to be a short version of similar kinetics observed during the development of poly(4-hydroxystyreneco-methacrylic acid) (PHSMA) film. 35) It was clearly observed that the thickness of the transient swelling layer was kept constant for a while during the development of PHSMA in diluted TMAH developer. This is typical for the dissolution with Case II diffusion.…”
Section: Resultsmentioning
confidence: 96%
“…This shoulder is considered to be a short version of similar kinetics observed during the development of poly(4-hydroxystyreneco-methacrylic acid) (PHSMA) film. 35) It was clearly observed that the thickness of the transient swelling layer was kept constant for a while during the development of PHSMA in diluted TMAH developer. This is typical for the dissolution with Case II diffusion.…”
Section: Resultsmentioning
confidence: 96%
“…13) The OH groups with pK a 4.76 are preferentially dissociated in the standard developer, while the OH groups with pK a 9.87 still maintain the hydrogen bonding. 15) This leads to the formation of a swelling layer thicker than in the case of PHS films. 15) Thus, in PHSMA, which is the most favorite base polymer for chemically amplified EUV resists, the OH groups that are not dissociated in the 2.38 wt% TMAH aqueous developer play an important role in the formation of the thick swelling layer.…”
Section: Introductionmentioning
confidence: 99%
“…15) This leads to the formation of a swelling layer thicker than in the case of PHS films. 15) Thus, in PHSMA, which is the most favorite base polymer for chemically amplified EUV resists, the OH groups that are not dissociated in the 2.38 wt% TMAH aqueous developer play an important role in the formation of the thick swelling layer. The control of the swelling layer caused by the phenolic OH groups is important for the suppression of resist pattern defects.…”
Section: Introductionmentioning
confidence: 99%